Telehealth in Response to the Rural Health Disparity - Shreya Kolluri; Thor S. Stead; Rohan K. Mangal; R. Lane Coffee Jr.; Jonathan Littell; Latha Ganti (Health Psychology Research)
The COVID-19 pandemic introduced lockdown and social distancing measures that made new methods of healthcare essential. Telehealth was introduced as a temporary measure but is being considered as a more permanent form of healthcare, particularly in rural areas, to provide more equitable healthcare. A survey was conducted on 200 rural dwellers (residents) regarding their experience with rural healthcare, any barriers to adequate healthcare, and openness to telehealth. The results demonstrated interest in telehealth and predominately positive experiences with telehealth in the areas where there was need and lack of access to healthcare, more commonly expressed in the younger age group. Quality healthcare should be equitable and available for every individual irrespective of zip code or the county they live. Telehealth is capable of bridging the gap of lack of access and transportation for individuals in rural areas to meet their healthcare needs in a timely fashion in the coming years.